Sleep Well to Perform Well: The association between sleep quality and medical student performance in a high-stakes clinical assessment. Issue 1 (30th June 2022) - Falloon, Karen; Bhoopatkar, Harsh; Moir, Fiona; Nakatsuji, Miriam; Wearn, Andy
Abstract: Study Objective: To investigate medical students' sleep quality and duration prior to a major clinical assessment, and their association with clinical performance. Methods: Third year medical students were surveyed following the end of year Observed Structured Clinical Examination (OSCE) using a self-completed questionnaire. The questionnaire focussed on sleep in the month and night before the assessment. OSCE scores were linked to questionnaire data for analysis. Results: The response rate was 76.6% (216/282). Poor sleep quality (Pittsburgh Sleep Quality Index > 5) was reported by 56.9% (123/216) and 34.7% (75/216) of students the month and night before the OSCE, respectively. Sleep quality the night before the OSCE was significantly associated with OSCE score ( P =0.038), but not sleep quality in the preceding month. The night before the OSCE, students obtained an average of 6.8 hours sleep (median 7, SD 1.5, range 2 to 12 hours). Short sleep duration (≤ 6 hours) was reported by 22.7% (49/216) and 38.4% (83/216) of students in the month and the night before the OSCE, respectively. Sleep duration the night before the OSCE was significantly associated with OSCE score ( P =0.026), but no significant association was found between OSCE score and sleep duration in the preceding month. Use of medication to help with sleep was reported by 18.1% (39/216) of students in the preceding month and by 10.6% (23/216) in the night before the OSCE. Conclusion: Medical students' sleep quality and duration the night before a clinical assessment were correlated with their performance in that assessment.